Sustainability models and indicators - Sakalauskas, Leonidas (Technological and Economic Development of Economy, 2010)
Achieving goals of sustainable development requires new models and indicators of gathering, sharing, and analyzing information, coordinating work, educating and training professionals, policymakers, and the public. Because of the complexity and the enormous amount of relevant data, the decision makers need effective support for their decisions. The use of a knowledge‐based approach is a solution for reducing this complexity. Nowadays the strategic and operational decisions are facing challenges of economic competition on a global perspective and realization of sustainable development that are the result of a new thinking and recognition of a competitive positioning, ecological and social consequences. Sustainable development is increasingly being seen as a major challenge in global terms. New information and communication systems build the bridge to on‐line and just‐in‐time decision‐making within supply chains and production and logistics networks. Operational Research has yet to be fully utilised in this area. To date, where it has been mostly used, it tends to deal with the relationships between environmental management and product supply chain and also focuses on the social dimension. This article surveys the recent work on sustainability models and indicators to be implemented in sustainability policies and decisions. Article in English. Tvarumo modeliai ir indikatoriai Santrauka. Darnusis vystymąsis tampa vis svarbesniu iššūkiu globaliu mastu. Darniojo vystymosi tikslams įgyvendinti reikia sukurti naujus informacijos kaupimo, paskirstymo ir analizės modelius bei indikatorius, skirtus profesionalams, vadybos specialistams ir visuomenei informuoti, koordinuoti bei mokyti. Dabartiniai strateginių ir operatyvinių sprendimų priėmimo metodai turi atsižvelgti į ekonominę konkurenciją globaliomis sąlygomis ir būtinuma įgyvendinti darniojo vystymosi sprendimus. Žinių technologijų naudojimas leidžia sukurti efektyvius dideliu įvairialypes informacijos kiekių apdorojimo metodus. Operaciju tyrimas (OT) gali ir turi būti pritaikomas aplinkosaugos vadyboje, gamybos “žaliose” grandyse ir socialineje sferoje. Naujos informacijos ir komunikacijų sistemos leidžia realizuoti laiku ir vietoje sprendimus, susijusius su tiekimo grandžiu vadyba bei produkcijos ir logistikos tinklais. Šiame darbe apžvelgiami modeliai ir indikatoriai, naudojami darniojo vystymosi politikai bei sprendimams įgyvendinti. Reikšminiai žodžiai: darnusis vystymasis, indikatoriai, daugiakriteriniai sprendimai, energijos planavimas, informacijos ir komunikacijų technologijos. First published online: 10 Feb 2011